Effect of friction coefficient change on internally shaped tubes drawing process using finite elements method. Issue 7 (20th July 2020) - Botko, F.; Bella, P.; Hatala, M.; Beraxa, P.; Lehocká, D.; Sutak, D.
Abstract: Presented article is focused on the effect of friction coefficient of drawing mandrel surface on parameters of the drawing process. Drawing of tubes with the internally shaped surface is complex problematics. Creation of internal ribbing is determined by many deformation zones which affect stress and strain acting in forming process. Finite elements method application on solving presented problematics gives the opportunity to simulate and optimize process without expensive prototype mandrels. Research if mainly focused on the shape and properties of drawing mandrel. For simulations purposes were selected three friction coefficients which are common in drawing process in dependence of tool surface and coating in combination with lubrication. Acquired results show behavior of strains and stresses in drawing process. Maximal values of observed parameters accompanied with jump changes are mostly pronounced in inner layer. Obtained values are applicable for setting of lubrication in drawing process from the perspective of elimination jump changes in stresses which can shorten life time of mandrel and lower quality of final product. Abstract : Presented article shows behavior of stress and strain in the wall of the shaped tube to extend knowledge of the forming process. Simulation of friction coefficient effect on forming process to describe drawing process of complex shaped parts. Results of simulations extend knowledge of forming process from the perspective of lubrication and selection of proper coating of tools.